PENGARUH STRES KERJA DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN ( STUDI PADA KARYAWAN PT. SURYA CIPTA INTERNUSA GRESIK) - CAHYANINGRUM, SYAMSIATUL (Jurnal Ilmu Manajemen (JIM), 2018)
In the era of globalization business competition is becoming increasingly tight. In order to compete competitively with other organizations, organizations in demand have adaptive and sensitive to changes that occur in the environment. By maximizing employees as human resources, the company will have qualified and skilled employees that can affect the improvement of employee performance. The current high job demands will affect the performance of its employees. If the demands of employees is higher and employees can not complete the work it will cause stress that affects the performance of employees is getting lower. Another thing that affects employee performance is work conflict. This study is to examine and analyze the effect of job stress on employee performance and work conflict on employee performance PT Surya Cipta Internusa Gresik. This research is quantitative research the number of samples used counted 48 people. The measuring instruments used in this study are interviews, observation, and questionnaires. Data analysis using Partial Least Square (PLS) analysis technique with the help of SmartPLS 3.0 and Statistical Package for Social Science (SPSS) software. This research uses Likert scale as measurement scale. The results showed that job stress negatively affect employee performance and work conflict positive and significant influence on employee performance. Keywords: Job Stress, Work Conflict, Employee Performance